Mathematics education research on algebra over the last two decades: quo vadis? - Veith, Joaquin Marc; Beste, Meeri-Liisa; Kindervater, Marco; Krause, Michel; Straulino, Michael; Greinert, Franziska; Bitzenbauer, Philipp (Frontiers in Education, 2023)
Algebra is a crucial component of mathematics education as it introduces learners to the mathematical world of modeling relationships and handling abstract quantities. The increasing volume of scholarly work in the field has been analysed qualitatively in numerous systematic reviews -a quantitative breakdown of the field, however, remains a desideratum to date. With this study we contribute to closing this gap by reporting on the results of a bibliometric analysis.We retrieved data from Scopus and Web of Science databases and analysed 1825 articles published between 2003 and 2022. On the one hand, we provide insight into the current state of algebra education from primary up to tertiary education by describing the scientific production and its bibliographic topography. On the other hand, we analysed the data to identify trends and future directions. The results of our study indicate, among other aspects, that APOS Theory and Realistic Mathematics Education are emerging themes in the field that have great potential to shape future research.